Wide Variations in Compliance with Tuberculosis Screening Guidelines and Tuberculosis Incidence between Antiretroviral Therapy Facilities — Côte d’Ivoire - Auld, Andrew F. (PLoS One, 2016)
BACKGROUND: In Côte d’Ivoire, tuberculosis (TB) is a common cause of death among HIV-infected antiretroviral therapy (ART) enrollees. Ivorian guidelines recommend screening for TB and initiation of TB treatment before ART initiation. Compliance with these guidelines can help reduce TB-related mortality during ART and possibly nosocomial TB transmission. METHODS AND FINDINGS: In a retrospective cohort study among 3,682 randomly selected adults (≥15 years old) starting ART during 2004–2007 at 34 randomly selected facilities, documentation of TB screening completion, prevalence of active TB at ART initiation, and incidence of TB during ART were evaluated. At ART initiation, median age was 36 years, 67% were female, and median CD4 count was 135 cells/μL. Among all 3,682 enrollees, 73 (2%) were on TB treatment at the time of referral to the ART facility. Among the 3,609 not on TB treatment, 1,263 (36%) were documented to receive some TB screening before ART initiation; 21% were screened for cough, 21% for weight loss, 18% for fever, 18% for TB contacts, and 12% for night sweats. Among the 1,263 screened, 111 (11%) were diagnosed with TB and started TB treatment before ART. No associations between patient characteristics and probability of being screened were noted. However, documentation of TB screening completion before ART varied widely by ART facility from 0–100%. TB incidence during ART was 3.0 per 100 person-years but varied widely by ART facility from 0/100 person-year to 13.1/100 person-years. CONCLUSIONS: Screening for TB before ART initiation was poorly documented. Facility-level variations in TB screening documentation suggest facility-level factors, such as investment in training programs, might determine documentation practices. Targeting under-performing ART facilities with improvement activities is needed. Variations among facilities in TB incidence warrant further research. These incidence variations could reflect differences between facilities in TB screening, diagnostic tests, documentation practices, or TB risk possibly related to infection control practices or local community TB incidence.